Diagnosis of Attention Deficit versus the Family as a Therapeutic Resource - Domínguez Sánchez, Cristina; Rodríguez Rodríguez, Alfonsa (Cuadernos de Trabajo Social, 2013)
This article is a reflection on the paradigm shift in the conceptualization of attention deficit disorder, having incorporated family assessment from a systemic perspective into the therapeutic approach, working not only with the patient exhibiting the symptoms, but also with the system within which the patient is embedded, that is, the nuclear family. The procedure done with a family who came to our office, desperate after years of enrollment in different treatments and therapeutic styles due to the illness of one of its members, will be analyzed.
Keywords: Systemic socio-family intervention; diagnosis; disorder; differentiation